Weight gain attempts and substance use behaviors among adults across five countries. (June 2022) - Ganson, Kyle T.; Nagata, Jason M.; Rodgers, Rachel F.; Cunningham, Mitchell L.; Lavender, Jason M.; Murray, Stuart B.; Hammond, David
Abstract: Weight gain attempts are common among adolescents, yet a paucity of research has explored these behaviors among adults, particularly in relation to substance use behaviors. To address this gap in the literature, pooled data from the 2018 and 2019 International Food Policy Study ( N = 42, 108) were analyzed. The association of weight gain attempts in the past 12 months with four important and relatively common substance use behaviors (alcohol use, binge-drinking, cigarette smoking, marijuana use) was examined using multiple modified Poisson regression analyses that adjusted for theoretically relevant covariates. Among men and women, weight gain attempts were associated with a higher likelihood of cigarette smoking in the past 30 days, marijuana use in the past 12 months, and binge-drinking one or more times per month in the past 12 months among men only. Among women, weight gain attempts were associated with a lower likelihood of alcohol use one or more times per month in the past 12 months. Our findings contribute to the literature demonstrating that substance use behaviors are more prevalent among adults who report weight gain attempts in a large international sample. Highlights: We analyzed data across five countries from the International Food Policy Study. Men and women who reported weight gain attempts also reported cigarette and marijuana use. Men who reported weight gain attempts were more likely to report binge-drinking. Women who reported weight gain attempts were less likely to report alcohol use.